2004
DOI: 10.1177/14746514040040040901
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain and insulin therapy

Abstract: Weight gain is common with insulin therapy in type 1 and type 2 diabetes. Excessive weight gain worsens glycaemic control and increases cardiovascular risk. It can also increase diabetic morbidity and mortality if it acts as a psychological barrier to initiation or intensification of insulin therapy, or affects compliance. Insulin-associated weight gain might result from conservation of previously excreted glucose, defensive `snacking' caused by fear or experience of hypoglycaemia, or the `unphysiological' pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…This finding is important considering that treatment with insulin has been associated with significant weight gain. 29 An important limitation of this study is that, although all efficacy and safety endpoints reported are in accordance with the respective protocol definitions of the two trials, analyses specifically addressing T2DM patients with CKD on insulin background therapy were retrospective in nature. It should also be noted that Study 1 and Study 2 were analysed separately.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is important considering that treatment with insulin has been associated with significant weight gain. 29 An important limitation of this study is that, although all efficacy and safety endpoints reported are in accordance with the respective protocol definitions of the two trials, analyses specifically addressing T2DM patients with CKD on insulin background therapy were retrospective in nature. It should also be noted that Study 1 and Study 2 were analysed separately.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, there is greater insulin in the periphery and less in the liver than normal. This situation may explain the increase in fat mass seen with insulin treatment 3 6 …”
Section: Introductionmentioning
confidence: 96%
“…In 2000, there were 171 million individuals with diabetes worldwide; it has been predicted that, by 2030, this will increase to 366 million 2 . More than 80% of patients with Type 2 DM (T2DM) are already overweight 3 . In addition, insulin and treatment with certain oral antidiabetic agents can cause weight gain, which makes reaching target glycemic levels difficult and increased diabetes‐associated morbidity and mortality 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations